2009
DOI: 10.1149/1.3111768
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Electrical Characteristics of High-k Sm[sub 2]TiO[sub 5] Gate Dielectrics

Abstract: A high-k Sm 2 TiO 5 gate dielectric was grown on silicon substrate through reactive cosputtering. We found that the Sm 2 TiO 5 dielectrics annealed at 800°C exhibited excellent electrical properties such as high capacitance value, almost no hysteresis voltage, small frequency dispersion, and low leakage current. This phenomenon is attributed to a rather well-crystallized Sm 2 TiO 5 structure and composition observed by X-ray diffraction and Auger electron spectroscopy, respectively.High-dielectric-constant ͑hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…[1][2][3][4][5][6][7] The applications of Ln 2 TiO 5 compounds range from high-permittivity dielectrics, biomedical sensing [1][2][3][4][5][6][7] to nuclear reactor control rod materials [8][9][10] and nuclear waste forms. 11 Lanthanide oxides as alloying constituents can be used as neutron absorbers in control rods.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7] The applications of Ln 2 TiO 5 compounds range from high-permittivity dielectrics, biomedical sensing [1][2][3][4][5][6][7] to nuclear reactor control rod materials [8][9][10] and nuclear waste forms. 11 Lanthanide oxides as alloying constituents can be used as neutron absorbers in control rods.…”
Section: Introductionmentioning
confidence: 99%
“…The dielectric was treated with post-RTA annealing as an effective method for lessening defect structures. In contrast to a previous study [9], the high-k Sm 2 TiO 5 capacitors fabricated on polysilicon substrate with proper RTA annealing show great promise for future generation CMOS devices.…”
Section: Introductionmentioning
confidence: 70%
“…Kim et al [22] reported that Sm 2 Ti 2 O 7 thin film in metal-insulator-metal capacitor has a high capacitance density and a low leakage current density. In addition, we demonstrated that thin Sm 2 TiO 5 film as gate dielectric materials showed a high capacitance value, a low hysteresis voltage, a small frequency dispersion, and a low leakage current [23]. Although the impact of Ti doping in the Sm 2 O 3 on electrical characteristics of IGZO TFTs was studied in our previous report [24], the physical and electrical properties of the Sm 2 TiO 5 film as a gate dielectric for -IGZO TFT devices are still not known.…”
Section: Introductionmentioning
confidence: 85%